2014
DOI: 10.1007/s12011-014-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Reduces Mobile Phone (900 MHz)-Induced Oxidative Stress, Mitochondrial Function, and Apoptosis in Breast Cancer Cells

Abstract: Exposure to mobile phone-induced electromagnetic radiation (EMR) may affect biological systems by increasing free oxygen radicals, apoptosis, and mitochondrial depolarization levels although selenium may modulate the values in cancer. The present study was designed to investigate the effects of 900 MHz radiation on the antioxidant redox system, apoptosis, and mitochondrial depolarization levels in MDA-MB-231 breast cancer cell line. Cultures of the cancer cells were divided into four main groups as controls, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 38 publications
0
21
0
2
Order By: Relevance
“…MSA significantly decreased E2-induced ROS accumulation of T47D breast cancer cells 21 . Selenite also inhibited electromagnetic radiation-induced oxidative stress and reduced the mitochondrial dysfunction in MDA-MB-231 cells 22 . By contrast, some studies showed that selenite exposure induce the apoptosis of cancer cells by producing superoxide radicals 23 , 24 .…”
Section: Discussionmentioning
confidence: 89%
“…MSA significantly decreased E2-induced ROS accumulation of T47D breast cancer cells 21 . Selenite also inhibited electromagnetic radiation-induced oxidative stress and reduced the mitochondrial dysfunction in MDA-MB-231 cells 22 . By contrast, some studies showed that selenite exposure induce the apoptosis of cancer cells by producing superoxide radicals 23 , 24 .…”
Section: Discussionmentioning
confidence: 89%
“…In addition, oxidative stress-induced apoptosis can be modulated by Ca 2+ release. The apoptosis and oxidative stress levels can be affected by the modulation of Ca 2+ entry through calcium channels, and some channels, such as voltage-gated and transient receptor potential melastatin 2 channels, are activated by oxidative stress, which can be modulated by selenium [8,12]. Selenium has both direct anti-cancer and chemotherapyintensifying effects when combined with conventional chemotherapeutic drugs [27].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-neoplastic mechanism of selenium compounds is considered to be associated with the prevention of copper-mediated DNA damage, inhibition of oxidation, promotion of cell apoptosis, and immune system regulation. However, the exact mechanisms are still unknown [8][9][10]. Selenium is known to have anti-angiogenic effects, and it can inhibit the growth of malignant cells by exerting cytotoxic activities [11].…”
Section: Introductionmentioning
confidence: 99%
“…The anticancer effects of cisplatin mediated by TRPV1 have to be potentiated by co-application of selenium or alpha-lipoic acid on MCF-7 breast cancer cells [128,129]. Interestingly, selenium was shown to diminish the electromagnetic radiation (900 MHz) effects in MDA-MB-231 breast cancer cell line mediated by TRPV1 activation [130].…”
Section: Trp Channels As Pharmacological Targets In Breast Cancermentioning
confidence: 99%